Factors Related to Adolescent Reproductive Health Behavior at SMKN I Subang, West Java Province in 2023 - Melysa Melysa; Laila Ulfa; Yuna Trisuci Aprilia (Universitas Ibn Khaldun Bogor, 2023)
Adolescents have a significant position in the development process because adolescents are the next generation of the nation. Health conditions, including reproductive health, are important. Based on interviews with 20 students, it was found that 80% of female students and 90% of male students had less knowledge about reproductive health behaviors. The purpose of this study was to determine the factors associated with adolescent reproductive health behavior. Mixed methods (sequential explanatory) research method cross-sectional research design. The population in this study is all grade X students of SMKN 1 Subang as many as 849 students. The research sample was class X as many as 201 students, quantitative sampling techniques purposive sampling, qualitative informants 6 people who had risky behavior. Analysis of univariate, bivariate data with chi-square test and multivariate with logical regression. The results of the bivariate analysis showed an association between sex (p-value = 0.000), exposure to information (p-value = 0.000), living with parents (p-value = 0.000), knowledge (p-value = 0.000), no attitude relationship (p-value = 0.171) access to health services with reproductive health behavior (p-value = 0.457). The dominant factor associated with reproductive health behavior is exposure to information (p-value = 0.000). The conclusion is that adolescent reproductive health behavior is greatly influenced by exposure to information. It is expected that the school will be able to collaborate and cooperate with the puskesmas to increase knowledge about reproductive health behavior, especially about sexually transmitted diseases through health counseling which is carried out a maximum of once every 3 months.